Bending and free vibration analysis of Levy-type porous functionally graded plate using state space approach. (1st March 2019) - Demirhan, Pinar Aydan; Taskin, Vedat
Abstract: This paper aims to investigate the free vibration and bending characteristics of porous functionally graded (FG) plate with two opposite simply supported edges based on a four variable plate theory. Material properties of porous FG plate are defined by rule of the mixture with an additional term of porosity in the through-thickness direction. Equations of motion are derived using Hamilton principle. State-space approach is used to obtain the governing equation of porous FG plate. The effect of porosity parameter, slenderness ratio, and the power-law index is investigated on bending and vibration of porous FG plate. The results are compared with available results in the literature to verify this theory.